2018
DOI: 10.1038/s41598-018-33486-9
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Modulates Post-Burn Lipolysis and Hepatic Fat Infiltration via Fatty Acid Synthase

Abstract: Burns result in generalized catabolism, lipolysis, and hyperinflammation. NLRP3 inflammasome, a mediator of hyperinflammation, is upregulated in burn patients’ adipose tissue within 7 days post-burn. However, its role during the acute phase is unknown. Here, wild-type (WT) and NLRP3 knockout (NLRP3−/−) mice were exposed to 25% TBSA scald burn. Flow cytometric analysis demonstrated greater liver macrophage infiltration in NLRP3−/− yet decreased protein expression of NLRP3 components, ER stress, and apoptosis. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Readouts such as elevated plasma IL-6 at 24 h post-insult, chronic inflammasome activation, loss of body mass, wound healing impaired by excessive angiogenesis, loss of glycaemic control, elevated markers of oxidative stress, immune dysregulation and neurodegenerative consequences, among others, have emerged as emblematic of the progression of PICS. [22][23][24][25][26][27] In a previous study, 15 the possible effect of iron in the efficacy of nephrilin peptide in a rat scald model was suggested. Here we show that, in both sexes of rats, the addition of equimolar ferric iron (but not ferrous iron or zinc) roughly doubles the efficacy of the peptide in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Readouts such as elevated plasma IL-6 at 24 h post-insult, chronic inflammasome activation, loss of body mass, wound healing impaired by excessive angiogenesis, loss of glycaemic control, elevated markers of oxidative stress, immune dysregulation and neurodegenerative consequences, among others, have emerged as emblematic of the progression of PICS. [22][23][24][25][26][27] In a previous study, 15 the possible effect of iron in the efficacy of nephrilin peptide in a rat scald model was suggested. Here we show that, in both sexes of rats, the addition of equimolar ferric iron (but not ferrous iron or zinc) roughly doubles the efficacy of the peptide in the model.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of caspase-1 occurs upon the activation of inflammasomes which induces the degradation of pro-caspase-1 (pro-form) to caspase-1 (active form) 4 . Therefore, the regulation of inflammasomes by pharmacological inhibitors is considered as an efficient strategy to reduce IL-1β levels in various inflammatory and immune diseases 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…DAMP molecules are known to significantly contribute to systemic inflammation and adverse outcomes in trauma [22, 23]. We have previously shown that NLRP3 activation is central to post-burn responses including the induction of ER stress and systemic inflammation [17, 24, 25]. Pro-inflammatory cytokines such as IL-6 and IL-1β can lead to ER stress highlighting a positive feedback loop promoting inflammatory signaling [2628].…”
Section: Introductionmentioning
confidence: 99%